CLONAL PROPAGATION OF JOJOBA BY IN VITRO CULTURE AND DETERMINATION OF SEXUALITY OF THE REGENERANTS - Z. Öncel; S. Erişen (Journal of Animal and Plant Sciences, 2017)
The present study was conducted to develop a protocol for in vitro propagation of Jojoba (Simmondsia chinensis) and to determine male and female regenerants through molecular markers. Nodal segments were cultured on MS media containing (0.5, 1.0, 2.0 mg/L) BAP, KIN or (0.22, 0.44, 0.88 mg/L) TDZ and 1.5, 2.0, 2.5 mg/L BAP or in combination with auxins (1.25 mg/L IAA, IBA, NAA) for in vitro propagation. As the result of the experiments, the highest number of shoots (9.13 shoots per explant) was obtained on MS medium containing 2.0 mg/L BAP. In vitro propagated shoots were transferred on MS media containing different concentrations of NAA, IAA and IBA for rooting. The best results were obtained on MS media containing 3.0 mg/L NAA or 1.0 mg/L IBA (40%, 30% respectively). The effect of ½ MS, 1.5% sucrose and active carbon addition (0.5%) on rooting was examined. The highest rooting rate (50%) was obtained on ½ MS medium containing 1 mg/L IBA, 1.5% sucrose and 0.5% active carbon. Rooted shoots were successfully acclimatised and showing on 75% survival rate. For sex determination, genomic DNA was isolated from the young leaves of male and female plants and regenerated shoots of unknown sex. PCR applications were performed by using UBC-807 and OPG-5 primers. UBC-807 produced a unique  ̴1,200 base-pair fragment in the male DNA. The determination of male and female individuals was successfully performed with the gel image obtained from UBC-807 primer.
Keywords: dioecious; DNA markers; micropropagation; sex identification; Simmondsia chinensis